2009
DOI: 10.4314/eajph.v5i3.39006
|View full text |Cite
|
Sign up to set email alerts
|

Social Factors, Social Support And Condom Use Behavior Among Young Urban Slum Inhabitants In Southwest Nigeria

Abstract: Objectives: Despite widespread knowledge that condoms offer protection against STIs/HIV when used correctly and consistently, many young people do not regularly use condoms, thus leading to new sexually transmitted infections, including HIV and AIDS. This study explored condom use behaviour, specifically the extent to which beliefs, self efficacy, risk perception and perceived social support act as predictors of use or non-use of condoms among sexually active young people aged 15-24 years. Methods: Data was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…The importance of a supportive environment of peers and social networks for condom use has been highlighted in past research which corroborates our study finding [14,[32][33][34]. This indicates that not only the personal motivation level of an individual, but also the perception that condom use is encouraged and approved by the people in the surroundings is important for consistent condom use.…”
Section: Discussionsupporting
confidence: 91%
“…The importance of a supportive environment of peers and social networks for condom use has been highlighted in past research which corroborates our study finding [14,[32][33][34]. This indicates that not only the personal motivation level of an individual, but also the perception that condom use is encouraged and approved by the people in the surroundings is important for consistent condom use.…”
Section: Discussionsupporting
confidence: 91%
“…17 However, despite the effectiveness of condoms in preventing unwanted pregnancies and STIs, condom use in South Africa has been described as declining among youths, and calls for a better understanding of how condoms fit within sexual practices. [18][19][20] In sub-Saharan Africa, the lethality of AIDS and risk of HIV acquisition in unprotected sex is almost universally known. The health-related behaviour model recognises that perception of being at risk as one of the necessary condition for adopting preventive behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also shown that while cost barriers persist in accessing discounted and free male condoms among low-wage users [21, 80], the cost of female condoms is approximately twelve times greater than male ones and often unaffordable for low-income consumers who find them acceptable to use [81]. Interestingly, a study in Nigeria observed that earning an income was marginally associated, but not statistically significant, with higher odds of male condom use among both slum adolescent boys and girls [82]. …”
Section: Discussionmentioning
confidence: 99%